Medullary Thyroid Carcinoma: Survival Analysis and Evaluation of Mutation-Specific Immunohistochemistry in Detection of Sporadic Disease - Jayakody, S.; Reagh, J.; Bullock, M.; Aniss, A.; Clifton-Bligh, R.; Learoyd, D.; Robinson, B.; Delbridge, L.; Sidhu, S.; Gill, A. J.; Sywak, M. (World journal of surgery, 2018)
Introduction Medullary thyroid cancer (MTC) is a rare tumour of neuroendocrine origin with a more aggressive profile than differentiated thyroid cancer. Familial cases of MTC are associated with RET mutations whilst RAS mutations appear to be a frequent finding in RET negative tumours. The aims of this study were to analyse survival outcomes in MTC and to evaluate the role of RAS immunohistochemistry in the identification of sporadic disease. Materials and methods A retrospective cohort study of consecutive patients with MTC was undertaken. The primary outcome measures were overall survival and disease-free survival. Survival analysis was performed on the basis of sporadic and familial disease. Patients had routine RET testing using the capillary (Sanger) sequencing method. Histopathological MTC slides from 100 patients were tested for HRASQ61R, a common somatic RAS mutation in MTC, with mutation-specific immunohistochemistry (IHC). Results A total of 195 patients had surgical treatment of MTC in the period 1980 to 2016. There were 83 males and 112 females with a mean age of 53.0 years. A total of 39 (20%) patients had familial disease. Sporadic cases had a higher median pre-op calcitonin (969.5 vs. 257.5 pg/ml), greater mean primary tumour size (23.5 vs. 12.5 mm) and more distant metastases (12.8 vs. 10.3%). Multivariate analysis showed age ( p = 0.005), Multiple Endocrine Neoplasia Type 2 (MEN2) status ( p = 0.021) and distant metastasis ( p = 0.002) to be significant independent predictors of survival. Significant independent predictors for disease-free survival were age ( p = 0.015), MEN2 ( p = 0.002), pre-op calcitonin ( p = 0.033) and venous invasion ( p = 0.001). The overall 5-year survival was 100% for familial MTC and 78% for sporadic MTC. The 10-year disease-free survival was 94% for familial MTC and 61% for sporadic cases. A total of 100 cases of MTC underwent mutation-specific IHC for HRASQ61R. Of these, 18 had confirmed MEN2. IHC had 100% specificity in excluding MEN2. Twelve (12%) of 100 patients stained positive for HRASQ61R mutation. Conclusion In the era of genetic testing, RET status significantly influences disease-specific survival in MTC. Mutation-specific IHC for HRASQ61R may have a role in the identification of patients presenting with sporadic disease.